THE USE OF SHORT STORIES AS MEDIA TO DEVELOP STUDENTS READING COMPREHENSION AT ELEVENT GRADE STUDENTS AT SMK KRISTEN 2 TOMOHON - Gersom Yos; Tini Mogea; Tirza Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research focus on the use of short stories as media to develop students' reading comprehension at elevent grade students at SMK Kristen 2 Tomohon. The research sample consisted of 20 students at class Fase F XI TJKT 1. A quantitative research method was used, employing a Pre-Experimental Design form of one group pre-test and post-test design. The instrument used in this research was a multiple-choice test consisting of 20 items. Data were analyzed using mean score formula to see significant differences between the pre-test and post-test scores. The results showed that there was a significant difference between pretest and posttest scores. The result of students’ pre-test was 44,1 and the post-test was 76,25. The different score between pre-test and post-test was 32,15. The result of this research is indicate that mean score of post-test was higher 32,15% more than pre-test. This shows that the use of short stories method is effective to develop students' reading comprehension at elevent grade students at SMK Kristen 2 Tomohon. In addition, students report that the short stories helps them to focus more and understand the text better. In conclusion, this research recommends that the short stories method be used as an alternative learning in teaching reading especially reading comprehension in schools.